ANALYSIS OF THE APPLICATION OF TAXES TO VILLAGE FUND MANAGEMENT - Kristina Wada Betu; Alfonsus Rodriques Suninono (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2024)
The purpose of this research is to examine how the implementation of taxation in South Biboki District, North Central Timor Regency, East Nusa Tenggara, over the past three years, from 2021 to 2023, has been conducted effectively and in accordance with the prevailing taxation laws and regulations. This research utilizes a qualitative research approach. The applied research method is qualitative descriptive method. The data collected involves both primary and secondary data, and adopts data collection techniques through interviews, observations, and documentation. The data sources obtained include both primary and secondary data sources. Based on the analysis results, the village of Upfaon has already conducted reporting and tax payment for village funds used in accordance with the prevailing tax laws and regulations. However, there are certain transactions that, due to limited understanding and awareness of tax obligations, have resulted in incorrect tax collection, deduction, payment, and reporting, thus disadvantaging state tax revenue and leading to additional expenditures from village funds that should not have been incurred. The implications of this study are that the Tax Service Office, Sub-district, and Regency need to provide special assistance in tax training to villages related to the management of village fund tax finances so that village officials are able to carry out their duties more effectively.